KEJADIAN STUNTING PADA BALITA DAN FAKTOR RISIKO - Soumokil, Octovina; Lestaluhu, Santi Aprilian; Anggraini, Vina; Noviani, Auliarinda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: West Golewa sub-district is one of the sub-districts located within the Mangulewa Health Center's working area. This area has a higher level of risk associated with stunting compared to other sub-districts under the management of other health centers in Ngada Regency. The aim of this study was to determine the risk factors associated with stunting. The research design used in this study was case control. The study was conducted in the Mangulewa Health Center Working Area, West Golewa District, Ngada Regency. The research was conducted in November 2023. The population in this study were all toddlers in West Golewa District as many as 788 children under five, with the number of stunted toddlers as many as 171 children under five and those who were not stunted as many as 617 children under five. The sample amounted to 104 consisting of 52 case samples and 52 control samples. The sampling technique used probability sampling with Simple Random Sampling technique. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed an association between the history of infectious diseases (p value: 0.000) with the incidence of stunting. It is recommended for mothers who have babies to routinely do posyandu in order to monitor the growth and development of their children and for health workers to be more active in socializing to the community about how to prevent stunting and fulfill nutrition in children.Keywords: Income, History of Infectious Disease, Stunting.